Effects of gamma irradiation on red blood cells at different storage period: A comparative study - Yousuf, Rabeya; Mobin, Mohd Herman; Subramaniam, Thirumeni; Leong, Chooi Fun (Bangladesh Journal of Medical Science, 2018)
Objectives: The objective of this study was to explore the effect of gamma irradiation on the haematological and biochemical parameters of the allogeneic red blood cells units at different storage duration. Methods: A prospective comparative study was conducted at the Blood Bank unit, Department of Diagnostic Laboratory Services of Universiti Kebangsaan Malaysia Medical Centre (UKMMC) in year 2013. Total 36 allogeneic red blood cell units were selected by simple random sampling method and divided into two groups, 18 units in each group based on the storage period into i) up to 14 days and ii) >14 days to expiry. Pre and post irradiation samples were taken immediately before and after irradiation of the units to analyse for the haematological parameters such as plasma Hb level, percent red cell haemolysis, haemoglobin per unit blood (Hb/unit), haematocrit (HCT), red cell indices such as mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC) and biochemical parameters such as plasma sodium (Na+), potassium (K+) and LDH levels. Data was collected and statistical analysis was done. Results: Statistically significant changes were observed between red cell units of up to 14 days and > 14 days old and pre irradiated samples in terms of plasma haemoglobin level, percent red cell haemolysis and plasma Na+, K+ and LDH levels. However, pre and post irradiation samples in each group of 14 days and >14 days showed significant changes in the plasma Hb and % haemolysis, Hb/unit, HCT, MCV and MCH in 14 days group while only in plasma Hb, MCV and MCH in >14 days group without any effect on plasma Na+, K+ and LDH levels in both group. Conclusion: Comparison at two different red cells storage groups i.e. period of up to 14 days and >14 days, showed significant changes in haematological and biochemical parameters. In the pre irradiation group this reflects the gradual storage changes over time even without going through the irradiation process. On the other hand, the changes between pre and post–irradiation for both the groups of storage showed significant haematological changes indicating irradiation itself also causes significant changes. In view of all these findings, we recommend to irradiate the allogeneic red cell units within 14 days of collection to reduce the adverse effects resulted from irradiation on the cellular products. Bangladesh Journal of Medical Science Vol.17(1) 2018 p.30-35